Ethics preparedness: facilitating ethics review during outbreaks - recommendations from an expert panel - Saxena, A; Horby, P; Amuasi, J; Aagaard, N; Köhler, J; Gooshki, E; Denis, E; Reis, A; Workshop, A; Ravinetto, R (BioMed Central, 2019)
BACKGROUND:Ensuring that countries have adequate research capacities is essential for an effective and efficient response to infectious disease outbreaks. The need for ethical principles and values embodied in international research ethics guidelines to be upheld during public health emergencies is widely recognized. Public health officials, researchers and other concerned stakeholders also have to carefully balance time and resources allocated to immediate treatment and control activities, with an approach that integrates research as part of the outbreak response. Under such circumstances, research "ethics preparedness" constitutes an important foundation for an effective response to infectious disease outbreaks and other health emergencies. MAIN TEXT:A two-day workshop was convened in March 2018 by the World Health Organisation Global Health Ethics Team and the African coaLition for Epidemic Research, Response and Training, with representatives of National Ethics Committees, to identify practical processes and procedures related to ethics review preparedness. The workshop considered five areas where work might be undertaken to facilitate rapid and sound ethics review: preparing national ethics committees for outbreak response; pre-review of protocols; multi-country review; coordination between national ethics committees and other key stakeholders; data and benefit sharing; and export of samples to third countries. In this paper, we present the recommendations that resulted from the workshop. In particular, the participants recommended that Ethics Committees would develop a formal national standard operating procedure for emergency response ethical review; that there is a need to clarify the terminology and expectations of pre-review of generic protocols and agree upon specific terminology; that there is a need to explore mechanisms for multi-country emergency ethical consultation, and to establish procedures for communication between national ethics committees and other oversight bodies and public health authorities. In addition, it was suggested that ethics committees should request from researchers, at a minimum, a preliminary data sharing and sample sharing plan that outlines the benefit to the population from which data and samples are to be drawn. This should be followed in due time by a full plan. CONCLUSION:It is hoped that the national ethics committees, supported by the WHO, relevant collaborative research consortia and external funding agencies, will work towards bringing these recommendations into practice, for supporting the conduct of effective research during outbreaks.